The incidence of depressive disorders in patients with schizophrenia - M. A. Novitskiy; N. A. Shnayder; R. F. Nasyrova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
Summary. Introduction. Historically, depressive disorders have been described in various forms of schizophrenia by Kraepelin (1923) or as a reaction to illness by Bleuler (1922). One of the alternative points of view that has been considered in recent years is that depressive disorders are a comorbid condition of schizophrenia or one of the manifestations of schizophrenia. However, to date, depression, as a symptom, is not included in the diagnostic criteria of the ICD-10. Methodological approaches to diagnosing depressive disorders in patients with schizophrenia differ in different countries and research groups. This influences the prevalence rates of depressive disorders in schizophrenic patients. Purpose. The study and systematization of studies of the incidence of depressive disorders in patients with schizophrenia.Methods. Russian-language and foreign literature was analyzed with a search depth of 10 years (2010–2020) in the following databases: PubMed, Springer, Wiley Online Library, Taylor & Francis Online, US National Library of Medicine National Institutes of Health, Science Direct and eLIBRARY .RU.Results. A total of 51 studies of depressive disorders in children and adults with schizophrenia were found.Conclusion. The frequency of occurrence of depressive disorders in patients with schizophrenia varies from 9.1 and to 100%, the average frequency is 41.6%. Their frequency is variable and depends on the region of residence and ethnicity. It is noted that depressive disorders in patients with schizophrenia are more often recorded among residents of the Middle East (72.7%), Russia (61.8%) and Europe (39.6%), less often among residents of Southeast Asia (32%) and the Pacific region ( 37.3%). The countries with the highest incidence of depressive disorders in schizophrenia include: USA, Germany, China; and to the countries with the lowest frequency — Denmark, Israel, South Africa. Also, I would like to note that the largest number of studies conducted was in Europe (16 studies with 36 928 patients with schizophrenia), the USA (6 studies with 2314 patients) and the Russian Federation (6 studies with 582 patients). In general, in the world, according to 51 studies analyzed, the incidence of depressive disorders in schizophrenia in men is higher than in women, although gender differences did not reach statistical significance in all regions of the world.